2023
DOI: 10.15252/embr.202255643
|View full text |Cite
|
Sign up to set email alerts
|

MYB sustains hypoxic survival of pancreatic cancer cells by facilitating metabolic reprogramming

Abstract: Extensive desmoplasia and poor vasculature renders pancreatic tumors severely hypoxic, contributing to their aggressiveness and therapy resistance. Here, we identify the HuR/MYB/HIF1a axis as a critical regulator of the metabolic plasticity and hypoxic survival of pancreatic cancer cells. HuR undergoes nuclear-to-cytoplasmic translocation under hypoxia and stabilizes MYB transcripts, while MYB transcriptionally upregulates HIF1a. Upon MYB silencing, pancreatic cancer cells fail to survive and adapt metabolical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…It is worth noting that MYB and STAG1 were found to regulate both DOCK8 and GIMAP5, implying that MYB and STAG1 may exert similar biological functions through these two genes. Anand found that MYB/HIF1α axis is a key regulator of metabolic plasticity and hypoxic survival in pancreatic cancer cells (Anand et al 2023). Giannini et al demonstrated that STAG1 is overexpressed in various tumors of reproductive system cancer and is associated with aberrant activation of the epidermal growth factor (EGF) pathway (Giannini et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that MYB and STAG1 were found to regulate both DOCK8 and GIMAP5, implying that MYB and STAG1 may exert similar biological functions through these two genes. Anand found that MYB/HIF1α axis is a key regulator of metabolic plasticity and hypoxic survival in pancreatic cancer cells (Anand et al 2023). Giannini et al demonstrated that STAG1 is overexpressed in various tumors of reproductive system cancer and is associated with aberrant activation of the epidermal growth factor (EGF) pathway (Giannini et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and western blotting were performed following a method as described earlier. 19 Briefly, cells were washed once with cold phosphate‐buffered saline (PBS) (Corning) and scraped into RIPA lysis buffer (Thermo Fischer Scientific) containing protease and phosphatase inhibitors. Cell lysates were sonicated and subsequently centrifuged at 13,400 g for 15 min at 4°C and supernatants were collected.…”
Section: Methodsmentioning
confidence: 99%
“…MYB is generally highly expressed in most pancreatic cancer cells, irrespective of gene amplification, and is responsible for promoting their growth and malignant properties [ 66 ]. Recent work has identified the role of MYB in the hypoxic survival of the cancer cells, mediated by its ability to stimulate HIF1a expression and function [ 67 ]. In prostate cancer, MYB was also initially found to be amplified, especially in hormone-refractory cancer cases [ 68 ].…”
Section: The Role Of Myb In Human Cancermentioning
confidence: 99%